Fruit and vegetables consumption is directly associated to survival after prostate cancer. Issue 4 (5th December 2016) - Taborelli, Martina; Polesel, Jerry; Parpinel, Maria; Stocco, Carmen; Birri, Silvia; Serraino, Diego; Zucchetto, Antonella
Abstract : In this cohort study on men with prostate cancer, elevated consumption of fruit and vegetables is associated with better prognosis. Consumption of foods rich in fiber and proanthocyanidins may halve the risk of death from all causes. High intakes of proanthocyanidins and flavonols are specifically associated with lower cancer‐specific mortality. Abstract : Scope: Since the evidence on the role of diet on prostate cancer (PCa) prognosis is still controversial, we evaluated the long‐term effects of fruit and vegetables consumption on survival after PCa. Methods and results: A retrospective cohort study included 777 men with PCa diagnosed between 1995 and 2002 in north‐eastern Italy and followed up to 2013. A validated food frequency questionnaire assessed the usual diet in the 2 years before PCa diagnosis, including detailed fruit and vegetables consumption. Adjusted hazard ratios (HRs) of death with 95% confidence intervals (CIs) were estimated using Fine–Gray models. PCa patients with a consumption of both fruit and vegetables above the median showed a higher 15‐year overall survival probability than those with lower intakes (71% versus 58%, p = 0.04; HR = 0.66, 95% CI: 0.47–0.93). Consumption of foods rich in fiber (HR = 0.59, 95% CI: 0.41–0.86) and proanthocyanidins (HR = 0.58, 95% CI: 0.40–0.82) were inversely associated with overall mortality. Interestingly, proanthocyanidins (HR = 0.52; 95% CI: 0.27–0.98) and flavonols (HR = 0.40; 95% CI: 0.19–0.84) were inversely associated also with PCa‐specific mortality. Conclusion: High consumption of fruit and vegetables offers an advantage in survival among the rising number of men living after a PCa diagnosis, possibly through the epigenetic effect of some nutrients.